Thyroid Fine-Needle Aspiration Cytology Practice in Korea - Yoon Jin Cha; Ju Yeon Pyo; SoonWon Hong; Jae Yeon Seok; Kyung-Ju Kim; Jee-Young Han; Jeong Mo Bae; Hyeong Ju Kwon; Yeejeong Kim; Kyueng-Whan Min; Soonae Oak; Sunhee Chang (Journal of Pathology and Translational Medicine, 2017)
We reviewed the current status of thyroid fine-needle aspiration cytology (FNAC) in Korea. Thyroid aspiration biopsy was first introduced in Korea in 1977. Currently, radiologists aspirate the thyroid nodule under the guidance of ultrasonography, and cytologic interpretation is only legally approved when a cytopathologist makes the diagnosis. In 2008, eight thyroid-related societies came together to form the Korean Thyroid Association. The Korean Society for Cytopathology and the endocrine pathology study group of the Korean Society for Pathologists have been updating the cytologic diagnostic guidelines. The Bethesda System for Reporting Thyroid Cytopathology was first introduced in 2009, and has been used by up to 94% of institutions by 2016. The average diagnosis rates are as follows for each category: I (12.4%), II (57.9%), III (10.4%), IV (2.9%), V (3.7%), and VI (12.7%). The malignancy rates in surgical cases are as follows for each category: I (28.7%), II (27.8%), III (50.6%), IV (52.3%), V (90.7%), and VI (100.0%). Liquid-based cytology has been used since 2010, and it was utilized by 68% of institutions in 2016. The categorization of thyroid lesions into “atypia of undetermined significance” or “follicular lesion of undetermined significance” is necessary to draw consensus in our society. Immunocytochemistry for galectin-3 and BRAF is used. Additionally, a molecular test for BRAF in thyroid FNACs is actively used. Core biopsies were performed in only 44% of institutions. Even the institutions that perform core biopsies only perform them for less than 3% of all FNACs. However, only 5% of institutions performed core biopsies up to three times more than FNAC.